Apoptotic Tumor Cell-Derived Extracellular Vesicles as Important Regulators of the Onco-Regenerative Niche - Gregory, Christopher D.; Dransfield, Ian (Frontiers in Immunology, 2018)
Cells undergoing apoptosis produce heterogeneous populations of membrane delimited extracellular vesicles (Apo-EVs) which vary, not only in size – from tens of nanometres to several microns – but also in molecular composition and cargo. Apo-EVs carry a variety of potentially biologically active components including small molecules, proteins and nucleic acids. Larger forms of Apo-EVs, commonly termed ‘apoptotic bodies’, can carry organelles such as mitochondria and nuclear fragments. Molecules displayed on the surface of EVs can contribute substantially to their size, as well as their functions. Thus far, relatively little is known of the functional significance of Apo-EVs apart from their roles in fragmentation of dying cells and indicated immunomodulatory activities. Here we discuss EV production by dying tumor cells and consider the possible roles of Apo-EVs in a cell death-driven sector of the tumor microenvironment known as the onco-regenerative niche (ORN). We propose that tumor-derived Apo-EVs are significant vehicles of the ORN, functioning as critical intercellular communicators that activate oncogenic tissue repair and regeneration pathways. We highlight important outstanding questions and suggest that Apo-EVs may harbor novel therapeutic targets.